2021
DOI: 10.1111/1759-7714.14217
|View full text |Cite
|
Sign up to set email alerts
|

Formation, contents, functions of exosomes and their potential in lung cancer diagnostics and therapeutics

Abstract: Lung cancer is the leading cause of cancer‐related death worldwide due to diagnosis in the advanced stage and drug resistance in the subsequent treatments. Development of novel diagnostic and therapeutic methods is urged to improve the disease outcome. Exosomes are nano‐sized vehicles which transport different types of biomolecules intercellularly, including DNA, RNA and proteins, and are implicated in cross‐talk between cells and their surrounding microenvironment. Tumor‐derived exosomes (TEXs) have been reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 165 publications
(282 reference statements)
0
11
0
Order By: Relevance
“…Crosstalk between cancer cells and the TME has been proven to play an important role in tumor progression and metastasis ( 43 ). And TIICs are an important component of the TME, and their composition and distribution are closely related to tumorigenesis and development ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crosstalk between cancer cells and the TME has been proven to play an important role in tumor progression and metastasis ( 43 ). And TIICs are an important component of the TME, and their composition and distribution are closely related to tumorigenesis and development ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…(C) GSVA analysis between the high-risk cohort and the low-risk cohort with KEGG. (43). And TIICs are an important component of the TME, and their composition and distribution are closely related to tumorigenesis and development (44).…”
Section: Functional Enrichment Analysis Of Smgsmentioning
confidence: 99%
“…It has been established that interaction between cancer cells and the TME is crucial for the development and spread of tumors ( 27 ). Additionally, TIICs represent a significant part of the TME, and the composition and location of these cells have a direct impact on the formation and occurrence of tumors ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…The R package “SingleR” is used for the annotation of different cell types ( 26 ). In addition, we used the “analyze_sc_clusters” function of the R package “ReactomeGSA” ( 27 ) for enrichment analysis and the “pathways” function to extract the results from different cells. Finally, the R packages “CellChat” ( 28 ) and “patchwork” were used for intercellular communication analysis and network visualization.…”
Section: Methodsmentioning
confidence: 99%
“…Containing various bioactive molecules including proteins, lipids, and nucleic acids, EVs not only mediate signal transduction in cellular communication but also participate in the physiological process including immune regulation and cancer progression [ 12 ]. Due to these characteristics, EVs could be a perfect mode of liquid biopsy, as reported by substantial evidence focusing on its clinical application in tumor diagnosis and prognosis [ 13 , 14 ]. However, no study has reported that EVs are associated with irAEs.…”
Section: Introductionmentioning
confidence: 99%